Implications of the introduction of laboratory demand management at primary care clinics in South Africa on laboratory expenditure - Ozayr H. Mahomed; Ruth Lekalakala; Shaidah Asmall; Naseem Cassim (AOSIS, 2016)
Background: Diagnostic health laboratory services are regarded as an integral part of the national health infrastructure across all countries. Clinical laboratory tests contribute substantially to health system goals of increasing quality of care and improving patient outcomes. Objectives: This study aimed to analyse current laboratory expenditures at the primary healthcare (PHC) level in South Africa as processed by the National Health Laboratory Service and to determine the potential cost savings of introducing laboratory demand management. Methods: A retrospective cross-sectional analysis of laboratory expenditures for the 2013/2014 financial year across 11 pilot National Health Insurance health districts was conducted. Laboratory expenditure tariff codes were cross-tabulated to the PHC essential laboratory tests list (ELL) to determine inappropriate testing. Data were analysed using a Microsoft Access database and Excel software. Results: Approximately R35 million South African Rand (10%) of the estimated R339 million in expenditures was for tests that were not listed within the ELL. Approximately 47% of expenditure was for laboratory tests that were indicated in the algorithmic management of patients on antiretroviral treatment. The other main cost drivers for non-ELL testing included full blood count and urea, as well as electrolyte profiles usually requested to support management of patients on antiretroviral treatment. Conclusions: Considerable annual savings of up to 10% in laboratory expenditure are possible at the PHC level by implementing laboratory demand management. In addition, to achieve these savings, a standardised PHC laboratory request form and some form of electronic gatekeeping system that must be supported by an educational component should be implemented.